Comparison of Antibiotic Sensitivity of Prevalent BacteriaIsolated from Urinary Tract Infections in 2002 and 2006 in Urmia, Iran: Antibiotic sensitivity and ressistance - Saber Yousefee; Mohammad Reza Nahaei; Bita Zareekar; Yaghoub Sharifi; Morteza Milani; Farzaneh Lotfipour (Iranian Journal of Pharmaceutical Sciences, 2009)
Urine specimens collected from in-patients and out-patients in Urmia Imam Hospital, northwest Iran, were cultured on blood agar and Eosin Methylene Blue agar. Isolated bacteria were identified according to standard microbiological tests and then subjected to sensitivity testing according to routine method of disk agar diffusion technique. Out of 8044 and 10425 urine specimens, 8.7% and 11.9% were identified as having urinary tract infection (UTI) in 2002 and 2006, respectively. The most prevalent bacteria belonged to enterobacteriaceae family and in the case of total susceptibility the upmost resistance was recorded against trimethoprim-sulfamethox-azole (62%) and gentamicin (50%) in 2002, and increased to 69% and 57% in 2006,respectively. The least resistance recorded was to ceftizoxim as 15.6% and 16.8 %in 2002 and 2006, respectively. Antibiotics susceptibility of in-patients wassignificantly lower than that of out-patients and this was more obvious for cephalosporins. Our findings show a remarkably high prevalence of resistance to the majority of commonly used antibiotics in UTIs, with a decreasing trend in their activities which probably is due to the high rate of antibiotics use in Iran as the first reason. Results of the present study underline the need for sensitivity tests prior to antibiotic therapy in UTI, which could help and guide in proper choosing of antibiotics and effective treatment and, therefore, prevention of antibiotic resistance.